Indirect Mutual Trust and Allowing Dynamic Data for Cloud Storage System (Global Journals of Research in Engineering, 2014)
Cloud Computing shifts the databases and application software to the centralized huge data centers, where the organization of the data and services can not be completely truthful. Different organizations generate a huge quantity of responsive data including private information, electronic health report, and economic information. A data owner paid for a desired level of protection and has to get some returns in case of any misbehavior dedicated by the cloud service providers (CSP). This work studies the difficulty of ensuring the reliability of data storage in Cloud Computing. In exacting, we consider the task of allowing a trusted third party (TTP), to confirm the reliability of the dynamic data stored in the cloud. Nearly all universal types of data operation, such as block insertion, deletion and modification, is also a important step toward reasonableness, while services in Cloud Computing are not limited to backup data or archive only. We studied cloud-based storage method so as to let the data owner to advantage from the services offered by the CSP and allows indirect mutual trust between data owner and CSP. It make sure that authoritative users (i.e., persons who have the right to access the owner#x2019;s data or files) obtain the most recent version of the outsourced data it permits the data owner to grant access or revoke access to the outsourced data.
Keywords: access control; cloud computing; data security; data outsourcing; cloud service provider; mutual trust